Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1108/ejm-04-2016-0228
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptualization of perceived complaint handling quality in social media and traditional service channels

Abstract: Purpose This study aims to conceptualize and test the effect of consumers’ perceptions of complaint handling quality (PCHQ) in both traditional and social media channels. Design/methodology/approach Study 1 systematically reviews the relevant literature and then carries out a consumer and manager survey. This approach aims to conceptualize the dimensionality of PCHQ. Study 2 tests the effect of PCHQ on key marketing outcomes. Using survey data from a German telecommunications company, the study provides an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 156 publications
(155 reference statements)
0
23
0
Order By: Relevance
“…Service recovery refers to any actions a service provider takes to resolve customer complaints and restore dissatisfied customers to a state of satisfaction (Gronroos, 1988). Reviews of service recovery strategies used by service providers in a social media setting identify that firms mostly use traditional service recovery approaches, which are typically based on the framework of distributional, procedural and interactional justice also common in face-to-face service encounters (Einwiller and Steilen, 2015; Hogreve et al , 2013; Sugathan et al , 2018). A few recent studies have considered the very public nature of social media to propose and empirically test updated service recovery strategies.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Service recovery refers to any actions a service provider takes to resolve customer complaints and restore dissatisfied customers to a state of satisfaction (Gronroos, 1988). Reviews of service recovery strategies used by service providers in a social media setting identify that firms mostly use traditional service recovery approaches, which are typically based on the framework of distributional, procedural and interactional justice also common in face-to-face service encounters (Einwiller and Steilen, 2015; Hogreve et al , 2013; Sugathan et al , 2018). A few recent studies have considered the very public nature of social media to propose and empirically test updated service recovery strategies.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Whilst the literature recommends that managers train employees in techniques to manage the misbehaviour of fellow consumers (Colm et al , 2017), there is scant research investigating strategies for managing VPOs on social media. Sugathan et al (2018) found that personalisation aids engagement and reciprocal relationships between consumers and employees and recommend that the employee should address the VPO with a personalised comment. Further, findings within the complaint literature indicate that when employees use an accommodative approach (including taking responsibility for the service failure, being apologetic and/or attempting to correct the service failure) customer satisfaction is positively affected (Einwiller and Steilen, 2015).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The presence of supportive VPOs has been shown to give the complainant greater perceived power, as collective public outrage is sometimes considered a motivational force for positive corporate change, in that, “[w]ithout outrage, companies are far less likely to clean up their acts” (Champoux et al , 2012, p. 22). Supportive VPOs may even assist in the complaint process by offering “resolution to doubts and queries” (Sugathan et al , 2018, p. 985).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…With increase in the social media usage for knowledge sharing, the stakeholders of higher education institutions would feel the importance of using the social media platform. The stakeholders’ (students, faculties and other administrative staffs of educational institutions) intention for knowledge sharing through other means, other than through social media platform, would not help them more to gain effective inputs from many other knowledgeable persons who might have previous experience in that issue of discussion (Sugathan et al , 2018; Seitz and Misra, 2020). Hence, the exchange of knowledge through social media appears to have additional advantage over and above other processes of sharing of knowledge, if the social media is trustworthy (Reagans and McEvly, 2003; Charband and Navimipour, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%